A theoretical assessment of the on-site monitoring of hydrogen-enriched natural gas by its thermodynamic properties - Jorge M. Monsalve (Frontiers in Energy Research)
A real-time, on-site monitoring of the concentration of hydrogen and the heating value of a blend of hydrogen and natural gas is of key importance for its safe distribution in existing pipelines, as proposed by the ‘Power-to-Gas’ concept. Although current gas chromatography (PGC) methods deliver this information accurately, they are unsuitable for a quick and pipeline-integrated measurement. We analyse the possibility to monitor this blend with a combination of sensors of thermodynamic properties—thermal conductivity, speed of sound and density—as a potential substitute for PGC. We propose a numerical method for this multi-sensor detection based on the assumption of ideal gas (i.e., low-pressure) behaviour, treating natural gas as a ‘mixture of mixtures’, depending on how many geographical sources are drawn upon for its distribution. By performing a Monte-Carlo simulation with known concentrations of natural gas proceeding from different European sources, we conclude that the combined measurement of thermal conductivity together with either speed of sound or density can yield a good estimation of both variables of interest (hydrogen concentration and heating value), even under variability in the composition of natural gas.